Penerapan Media Gambar Dalam Kegiatan Ekstrakurikuler Bahasa Inggris Siswa Madrasah Ibtidaiyah - Hastuti, Hilda; Fatimatuzzahra; Agus Syahid; Fitri Apriliany; Recta Olivia Umboro (Insan Kreasi Media, 2023)
The development of information technology requires teachers to be able to present more interesting English language learning. Picture is a learning medium that can be used as a strategy in learning English at MI NW Karang Bata Mataram. The methods used are (1) Problem identification, at this stage observations are made at the school and analysis of student needs to determine the initial needs of MI NW Karang Bata students regarding materials, media and methods used; (2) the solution offered is picture and game based learning methods. The 'Read for Me' game is an appropriate method to use to make students more interested in learning English; (3) Picture is very helpful for teachers and students in the learning process, because elementary students level need concrete media to be able to understand the information or concepts provided. The aim of this devotion is to create learning that can build students' motivation and interest in learning. The results of the implementation of this service show that the application of image media using the 'Read For Me' game method can create more interesting English learning so as to increase students' motivation and interest in learning English